Quasi‐chipless wireless temperature sensor based on harmonic radar. Issue 2 (1st January 2014) - Kubina, B.; Romeu, J.; Mandel, C.; Schüßler, M.; Jakoby, R.
Abstract : A novel passive wireless temperature sensor is presented, which aims at operating in harsh environments. For this purpose, the tag is designed quasi‐chipless and it uses a harmonic radar sensing principle: it combines the backscattering on the first harmonic of the transmitted frequency with frequency‐position encoding of the measured value. The harmonic radar approach brings significant advantages for the wireless readout, since it isolates the undesired radar clutter from the useful tag signal. The tag signal carries the desired temperature information encoded in the position of a resonance transmission peak. The tag is built up planar and consists of two patch antennas, a temperature‐dependent bandpass filter and a diode‐based harmonic generator. It works at 1.59 GHz and backscatters at 3.18 GHz. Wireless indoor measurements have proven the concept. The sensor has shown a temperature sensitivity of 1.2 MHz/K in the range of 22–109 °C.